2D/3D boundary element programming in petroleum engineering and geomechanics - Morita, Nobuo (Developments in petroleum science, 2020)
2D/3D Boundary Element Programming in Petroleum Engineering and Geomechanics, Volume 70, is designed to make it easy for researchers, engineers and students to begin writing boundary element programs. This reference covers the fundamentals, theoretical developments, programming and applications. Both fluid flow through porous media and structural problems are used for coding exercises. Included computer programs may be used as starting codes; after modifications, they can be applied to real world problems. The book covers topics around mesh generation, 3D boundary element coding, and interface coding for controlling mesh generation, and plotting results.